Engineering International Norm Emergence in Cryptocurrency - Blahoš, Vojtěch; Trávníčková, Zuzana, 1977-; Rolenc, Jan Martin, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The thesis employs a theoretical framework to investigate the development of international norms in cryptocurrency regulation. The framework delineates three critical stages—Detection, Evaluation, and Convergence—which the author uses as a basis to categorize and analyze the global landscape of cryptocurrency regulation. Countries were identified in all of the stages of the development of a norm. However, the vast majority of the world belongs to the second stage, Evaluation. A substantial proportion of countries are in the midst of ongoing evaluation, as there is still a de facto ambiguity towards cryptocurrency, and no further steps have been taken to enact comprehensive regulation. There are also countries that perceive cryptocurrency as beneficial or detrimental. Nevertheless, their regulations do not reflect societal norms. Additionally, the thesis identified only two regulators that have reached the final Convergence stage: the UK and, more importantly, the EU and its Markets in Crypto-Assets Regulation (MiCA). The thesis proposes that MiCA may serve as a pioneering model, as it has the potential to be a template for global cryptocurrency regulation, given the EU's status as a normative power. The methodology employs a Synthesized Regulatory Framework Analysis, which integrates qualitative and quantitative data to accurately categorize countries within the identified stages of the theoretical framework.
Vedoucí práce: Zuzana Trávníčková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses